Penambahan agar-agar dan pengaruhnya terhadap kestabilan dan daya terima susu tempe pada mahasiswa Politeknik Kesehatan Jurusan Gizi Yogyakarta - Isti Suryani; Agus Santoso; Muhammad Juffrie (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: The production of tempeh milk is an effort to diversify tempeh-based food processing potential as functional food. However, as vegetable milk tempeh milk has the disadvantages of tasting bitter and being easily precipitate. The addition of gelatine is potential as stabilizer that is expected to counter the disadvantages and improve the taste of tempeh milk.Objective: To identify the effect of gelatine addition to stability and acceptability of tempeh milk among students of Nutrition Department of Health Polytechnic Yogyakarta.Method: The study was experimental with a completely randomized design, comprising four experiments, i.e. tempeh milk with gelatine addition as much as 2%, 3%, 4% and no gelatine addition as control. Organoleptic test was made by 25 skilled panelist, students of Nutrition Department of Health Polytechnic Yogyakarta, to identify acceptability of tempeh milk. Whereas viscocity test and visual observation through the assessment of tempeh milk precipitation level within 5 hours storage were made to identify emulsion stability. Data analysis used Anova and Duncan advanced test.Result: Stable emulsion could be achieved through gelatine addition of 2% at emulsion consistency 89.10%, viscocity 0.225 poise. Better emulsion stability was achieved through gelatine addition of 3% at emulsion consistency 91.10%, viscocity 0.249 poise. Best emulsion stability was achieved through gelatine addition of 4% at emulsion consistency 95.58%, viscocity 0.254 poise and lowest emulsion stability was found in the control without gelatine addition at emulsion consistency 80.84%, viscocity 0.216 poise. The result of proximate nutrition value of tempeh milk with gelatine addition 4% (most stable) were energy 55.54 cal, protein 2.14gr, fat 1.82g, carbohydrate 7.65%, water 86.23g, ash 0.15% and raw fbre 2.01%.Conclusion: There was no effect of gelatine addition at various concentration to acceptability of tempeh milk. There was effect of gelatine addition at various concentration to stability of tempeh milk. The highest emulsion stability was achieved in tempeh milk with gelatine addition of 4%.